Analisis Pengaruh Kebijakan Keuangan Terhadap Profitabilitas dengan Kebijakan Penurunan Tarif PPh Badan Sebagai Variabel Moderasi - Riztari Anggraini; Andewi Rokhmawati; Poppy Nurmayanti (Jurnal EMT KITA, 2023)
This study aims to examine the effect of financial management policies on profitability. Apart from that, the effect of each independent variable on the dependent was tested with a decrease in corporate income tax rates as a moderating variable. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2020. There are 96 samples that meet the following criteria; manufacturing companies whose 2019 and 2020 financial statements are available on the IDX, manufacturing companies that do not suffer losses and manufacturing companies that do not have interest write-off income on debt restructuring. This research was analyzed using Multiple Regression Analysis. The results of this study state that the dividend distribution policy has a positive effect on profitability, an increase in debt has a negative effect on profitability, an increase in investment has a positive effect on profitability, a decrease in corporate income tax rates is not able to moderate the effect of dividend distribution policies on profitability, a decrease in corporate income tax rates can strengthen the effect of funding policy on profitability, lower corporate income tax rates weakened the effect of funding policy on profitability.